Women's perspective in Mujeres de ojos grandes, by Ángeles Mastretta (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
Mexican writer Ángeles Mastretta, with a spare style and irony, narrates the strategies used by a group of brave, modern, and rebellious Mexican women in order to achieve a space of freedom in their lives, in spite of living in the Mexican society of the first third of the 20th century dominated by masculine hegemony.
Keywords: women; feminism; equality; rupture; freedom